The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 1st International Conference on Designing Interactive User Experiences for TV and Video 2008
DOI: 10.1145/1453805.1453809
|View full text |Cite
|
Sign up to set email alerts
|

How text and audio chat change the online video experience

Abstract: Many online video sites provide a text chat feature so viewers can chat with others while watching videos. How does chatting affect their experience? Would audio chat be more fun or would it be too distracting? The richer medium of audio may more closely approximate the living room or club experience, but human factors research suggests that audio chat could increase distraction and detract from the viewing experience. This paper presents the results of an experiment comparing text with audio chat when the vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
9
3
Order By: Relevance
“…For instance, De Souza [6,23] and the Semiotic Engineering Research Group (SERG) have been using tagging in ''communicability analyses'' to trace communicative breakdowns during interaction, categorizing observable user utterances and interactions. Also, Ducheneaut [8] and Weisz [27] have used conversation tagging in the context of interactive television chat applications.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, De Souza [6,23] and the Semiotic Engineering Research Group (SERG) have been using tagging in ''communicability analyses'' to trace communicative breakdowns during interaction, categorizing observable user utterances and interactions. Also, Ducheneaut [8] and Weisz [27] have used conversation tagging in the context of interactive television chat applications.…”
Section: Discussionmentioning
confidence: 99%
“…Ames and colleagues (2010) note that video communication by family members acts to "reinforce their identity as a family and reinforce their family values" (p. 145). Studies have also examined the extent to which people can build social capital while watching videos, focusing on social or interactive video-sharing (Agamanolis, 2008;Guha, 2008;Oumard, Mirza, Kroy, & chorianopoulos, 2008;weisz, 2008;weisz & Kiesler, 2008). Scholars have suggested that most people share online videos with their families and friends (Guha, 2008;Oumard et al, 2008) by forwarding the link, discussing a video they have seen, or watching it with others (weisz, 2008).…”
Section: Online Communication For Social Connectionmentioning
confidence: 99%
“…A 2008 study found that participants were multitasking while watching online videos, such as instant messaging, emailing, or talking on the phone or in person (weisz, 2008). Such activities, as well as recommending videos, could aid in maintaining or building relationships (weisz & Kiesler, 2008). …”
Section: Online Communication For Social Connectionmentioning
confidence: 99%
“…Weisz and Kiesler [36] discussed about evidences that a text chat feature is warranted as part of an online video experience. Even though they found evidence that chat is distracting, participants enjoyed using the chat feature, and the distraction did not diminish their video or overall enjoyment [36].…”
Section: Related Workmentioning
confidence: 99%
“…Even though they found evidence that chat is distracting, participants enjoyed using the chat feature, and the distraction did not diminish their video or overall enjoyment [36]. The possibility of chatting when watching a video record can enrich users' view, by commenting about the experience, but also disturb their attention in the contentwith the CWaCTool, users can pause the exhibition in order to comment and after this replay the video file.…”
Section: Related Workmentioning
confidence: 99%